Low energy availability in athletes: A review of prevalence, dietary patterns, physiological health, and sports performance - Logue, D.; Madigan, S. M.; Delahunt, E.; Heinen, M.; Mc Donnell, S.-J.; Corish, C. A. (Sports Medicine, 2018)
In a high-performance sports environment, athletes can present with low energy availability (LEA) for a variety of reasons, ranging from not consuming enough food for their specific energy requirements to disordered eating behaviors. Both male and female high-performance athletes are at risk of LEA. Longstanding LEA can cause unfavorable physiological and psychological outcomes which have the potential to impair an athlete`s health and sports performance. This narrative review summarizes the prevalence of LEA and its associations with athlete health and sports performance. It is evident in the published scientific literature that the methods used to determine LEA and its associated health outcomes vary. This contributes to poor recognition of the condition and its sequelae. This review also identifies interventions designed to improve health outcomes in athletes with LEA and indicates areas which warrant further investigation. While return-to-play guidelines have been developed for healthcare professionals to manage LEA in athletes, behavioral interventions to prevent the condition and manage its associated negative health and performance outcomes are required.